Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/neuonc/noab114
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C silencing downregulates NF2 and E-cadherin and enhances Erastin-induced ferroptosis in meningioma

Abstract: Background Ferroptosis, a programmed cell death characterized by lipid peroxidation, is implicated in various diseases including cancer. Although cell density-dependent E-cadherin and Merlin/Neurofibromin (NF2) loss can modulate ferroptosis, the role of ferroptosis and its potential link to NF2 status and E-cadherin expression in meningioma remain unknown. Methods Relationship between ferroptosis modulators expression and NF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 38 publications
1
31
1
4
Order By: Relevance
“…Notably, the dose of erastin (10 mg/kg, i.p., twice every other day) we explored and used in treating glioma was lower than that we used in meningioma treatment before, which was 15 mg/kg, i.p., twice every other day [49]. Moreover, compared with the data published before, we found that Sun X used 20 mg/kg intravenously (i.v.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, the dose of erastin (10 mg/kg, i.p., twice every other day) we explored and used in treating glioma was lower than that we used in meningioma treatment before, which was 15 mg/kg, i.p., twice every other day [49]. Moreover, compared with the data published before, we found that Sun X used 20 mg/kg intravenously (i.v.…”
Section: Discussionsupporting
confidence: 50%
“…This suggests that oxidation of SOX2 could be a potential target for ferroptosis-targeted treatment for cancer (130). Moreover, as cell density-dependent E-cadherin and Merlin/Neurofibromin (NF2) loss can induce ferroptosis, Bao et al found that NF2-inactivated meningioma cells were sensitive to Erastin-induced ferroptosis by analyzing 35 meningioma samples (10 NF2 loss and 25 NF2 wildtype), and further confirmed that myoenhancer factor 2C (MEF2C) acted as a promoter of NF2 and CDH1, thereby inhibiting ferroptosisrelated lipid peroxidation and meningioma cell death (131). Notably, Kremer et al indicated that aspartate aminotransferase (GOT1) could damage mitochondrial oxidative phosphorylation and promote catabolism, resulting in the increase of unstable iron pool and susceptibility to ferroptosis, this effect suggests that inhibiting GOT1 could destroy the redox balance and proliferation in pancreatic ductal carcinoma, and establishes a biochemical link between GOT1 and ferroptosis (132).…”
Section: Iron and Ferroptosismentioning
confidence: 92%
“…Moreover, as cell density-dependent E-cadherin and Merlin/Neurofibromin (NF2) loss can induce ferroptosis, Bao et al. found that NF2-inactivated meningioma cells were sensitive to Erastin-induced ferroptosis by analyzing 35 meningioma samples (10 NF2 loss and 25 NF2 wildtype), and further confirmed that myoenhancer factor 2C ( MEF2C) acted as a promoter of NF2 and CDH1 , thereby inhibiting ferroptosis-related lipid peroxidation and meningioma cell death ( 131 ). Notably, Kremer et al.…”
Section: Iron and Cell Deathmentioning
confidence: 92%
“…Silencing MEF2C, the expression levels of NF2 and E-cadherin in meningiomas decreased, which inhibited the growth of meningiomas mediated by ferroptosis ( Figure 1 ). Therefore, MEF2C can be used as a potential molecular target for the treatment of aggressive meningiomas through modulating ferroptosis ( 107 ).…”
Section: Ferroptosis and Transporters In Malignant Brain Tumorsmentioning
confidence: 99%